Integrasi Delone & McLean dengan UTAUT2 untuk Evaluasi Perilaku Penggunaan Access by KAI - Hidayat, Alifiansyah Arrizqy; Rospricilia, Tita Ayu (INTEGER: Journal of Information Technology, 2025)
Business is a human activity that aims to profit through producing and distributing goods or services. In the world of transportation, mobile technology increasingly provides opportunities, especially in booking transportation tickets. One of the latest innovations is the Access by KAI application developed by PT KAI to meet the needs of train passengers. However, it has not been able to attract consumer interest as much as other ticket-booking applications. Based on a survey, the percentage of Access by KAI usage is still relatively low compared to other platforms such as Traveloka and Tiket.com. This shows a challenge for PT KAI in increasing the attractiveness of the application in order to compete with other, more popular applications. This study aims to evaluate the behavior of KAI application users regarding access by developing a conceptual model that integrates variables in the DeLone and McLean model with UTAUT2 to understand the factors that influence the application's success in meeting user expectations and increasing user satisfaction. The method used in this study combines the DeLone and McLean model to measure the quality of information systems and the UTAUT2 model to analyze factors of technology acceptance by users. The results of the study show that service quality, user satisfaction, performance expectancy, effort expectancy, and price value significantly influence behavioral intention. In addition, it was found that user satisfaction is significantly influenced by service quality.